Impact of Timing of Adjuvant Chemoradiation for Glioblastoma in a Large Hospital Database. Issue 5 (28th October 2017) - Osborn, Virginia W; Lee, Anna; Garay, Elizabeth; Safdieh, Joseph; Schreiber, David
Abstract: BACKGROUND: Although the standard of care for glioblastoma remains maximal safe resection followed by chemoradiation, conflicting reports have emerged regarding the importance of the time interval between these 2 treatments. OBJECTIVE: To assess whether differences in the duration between surgery and initiation of chemoradiation for glioblastoma had an impact on overall survival (OS) in a large hospital-based database. METHODS: The National Cancer Database was queried to identify patients diagnosed with glioblastoma between 2010 and 2012 treated with surgery followed by chemoradiation. Patients who received biopsy only were excluded. The time from surgery to initiation of radiation therapy was divided into 4 equal quartiles of ≤24, 25 to 30, 31 to 37, and >37 d. Patient characteristics were compared between groups using Pearson Chi Square and Fisher's Exact test. OS was analyzed via the Kaplan–Meier method and compared via the log-rank test. Univariable and multivariable Cox regression were performed to assess for impact of covariables on OS. RESULTS: A total of 11 652 patients were included in the analysis. Median duration from surgery to radiation was 30 d. On multivariable regression, black race, larger tumor, gross-total resection, methyguanine-methyl transferase (MGMT+), and treatment at an academic facility were associated with a duration >30 d. On multivariable analysis, there were no significant differences when comparing start within 24 d to 25 to 30 d (hazard ratio [HR] 0.96, 95% confidence interval [CI] 0.90-1.01, P = .13) or > 37 d (HR 0.97, 95% CI 0.91-1.03, P = .26), although a small OS improvement was seen if initiated within 31 to 37 d (HR 0.93, 95% CI 0.88-0.99, P = .02). CONCLUSION: There was no clear association between duration from surgery to initiation of chemoradiation on OS.